2012
DOI: 10.1186/1471-2261-12-11
|View full text |Cite
|
Sign up to set email alerts
|

QT dispersion in patients with systemic lupus erythematosus: the impact of disease activity

Abstract: BackgroundPatients with systemic lupus erythematosus (SLE) have increased cardiovascular morbidity and mortality. Although autopsy studies have documented that the heart is affected in most SLE patients, clinical manifestations occur in less than 10%. QT dispersion is a new parameter that can be used to assess homogeneity of cardiac repolarization and autonomic function. We compared the increase in QT dispersion in SLE patients with high disease activity and mild or moderate disease activity.Methods and Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…28 Heart rhythm disorders can be related with CAD, myocarditis, or small vessel vasculitis with collagen deposition and fibrosis affecting the conduction system in SLE. 16,17 In our study, we found significant differences in QTd and cQTd between SLE patients and control group. 16,17 In our study, we found significant differences in QTd and cQTd between SLE patients and control group.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…28 Heart rhythm disorders can be related with CAD, myocarditis, or small vessel vasculitis with collagen deposition and fibrosis affecting the conduction system in SLE. 16,17 In our study, we found significant differences in QTd and cQTd between SLE patients and control group. 16,17 In our study, we found significant differences in QTd and cQTd between SLE patients and control group.…”
Section: Discussionsupporting
confidence: 50%
“…The QT duration, in particular heart rate-corrected QT interval duration and QT dispersion remain the most common measure for repolarization abnormalities both in clinical and research settings. 17 Prolonged QTd and cQTd that we found in our study may reflect silent myocardial involvement in SLE patients. 16 Kojuri et al reported that QTd was significantly increased in SLE patients with high disease activity compared to patients with low disease activity.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…It is known that QTc length and QT dispersion correlate with disease activity and cytokine levels in both patients with SLE and patients with RA 711 30 48–51 We used the SLEDAI-2K, DAS28-CRP and CRP levels (as well as IL-6 levels in the RA group) to estimate disease activity. CRP levels were lower in the RA cohort as compared with the SLE cohort, and the IL-6 levels in the RA group were approximately three times lower than what has been reported in patients with active disease 52.…”
Section: Discussionmentioning
confidence: 99%